Pelaksanaan Pembinaan Pegawai Negeri Sipil Dalam Upaya Meningkatkan Disiplin Kerja Pegawai Pada Kantor Camat Kadia Kota Kendari - Widiani, Cindy Clara; Alam, Syamsul; Yusuf, Muhammad (REZ PUBLICA, 2021)
The purpose of this study was to identify and describe the implementation of civil servant coaching in an effort to improve work discipline at the Kadia Sub-district Office, Kendari City. The results of this study indicate that; 1) efforts to implement supervision through observation, inspection and monitoring at the Kendari District Head Office are generally quite optimal. Where the leadership sometimes makes observations on the accuracy of employees in working and the implementation of assigned employee duties, and sometimes checks the attendance of employees. But on the other hand, the leadership always checks the work results of employees, monitors the use of work facilities and monitors the accuracy of the implementation of tasks, 2) the effort to implement supervision is enough to increase the work discipline of employees at the Kendari District Head Office. Where there is a condition that there is still a lack of employee obedience to working hours, and the implementation of work is sufficient based on work procedures / mechanisms. But on the other hand, employees at the Kendari sub-district office show an understanding of their respective main duties and work procedures / mechanisms, and always maintain politeness and ethics. The purpose of this study was to identify and describe the implementation of civil servant coaching in an effort to improve work discipline at the Kadia Sub-district Office, Kendari City. The results of this study indicate that; 1) efforts to implement supervision through observation, inspection and monitoring at the Kendari District Head Office are generally quite optimal. Where the leadership sometimes makes observations on the accuracy of employees in working and the implementation of assigned employee duties, and sometimes checks the attendance of employees. But on the other hand, the leadership always checks the work results of employees, monitors the use of work facilities and monitors the accuracy of the implementation of tasks, 2) the effort to implement supervision is enough to increase the work discipline of employees at the Kendari District Head Office. Where there is a condition that there is still a lack of employee obedience to working hours, and the implementation of work is sufficient based on work procedures / mechanisms. But on the other hand, employees at the Kendari sub-district office show an understanding of their respective main duties and work procedures / mechanisms, and always maintain politeness and ethics.